Exploring unmet needs and preferences of young adult stroke patients for post-stroke care through PROMs and gender differences - Ibrahim, Sarah; Francis, Troy; Sheehan, Kathleen A.; Kokorelias, Kristina; Stanimirovic, Aleksandra; Hashmi, Syeda; Kalocsai, Csilla; Ng, Sharon; Berkhout, Suze G.; Cameron, Jill I.; Rac, Valeria; Pikula, Aleksandra (Frontiers in Stroke, 2024)
Background Stroke incidence among young adults of working age (under 65 years of age) has significantly increased in the past decade, with major individual, social, and economic implications. There is a paucity of research exploring the needs of this patient population. This study assessed: (1) young adult stroke patients' physical, psychological, and occupational functioning and health-related quality of life (HRQoL); and (2) post-stroke care preferences using patient-reported outcome measures (PROMs), with attention to gender differences. Methods A cross-sectional pilot study was conducted. Sociodemographic and clinical characteristics were collected through chart review and data on occupational function, physical, psychological, and social wellbeing >90 days post-stroke through a self-reported survey. Descriptive statistics, gender-based, and regression analyses were conducted. Results The sample included 85 participants. Participants reported impairments in both, occupational functioning, with 58.7% not returned to work (RTW), and HRQoL, specifically with social activities (37%), anxiety (34%), and cognitive function (34%). Women had significantly (p < 0.05) worse physical symptoms (sleep disturbance and fatigue), emotional health (depression, stigma, emotional dyscontrol) scores, and sense of self-identify post-stroke. Over 70% of participants preferred in-person post-stroke care led by health care providers and felt they would have benefited from receiving information on physical health (71.4%), emotional and psychological health (56.0%), RTW (38.1%), and self-identity (26.2%) post-stroke. Women preferred cognitive behavioral therapy (p = 0.018) and mindfulness-based stress reduction therapy (p = 0.016), while men preferred pharmacotherapy (p = 0.02) for psychological symptoms. Conclusion This is the first study to report impaired HRQoL, psychological and occupational functioning using PROMs, with significant gender differences and preferences for post-stroke care delivery among young adult stroke patients at >90 days after stroke. The findings highlight the importance of needs, gender, and age-specific post-stroke education and interventions.